Reconstruction of Personal Didactic Models of Biology Novice Teachers Reconstrucción de Modelos Didácticos Personales de Profesoras Noveles de Biología - Pesciallo, Fernanda (2022)
This work aims to give visibility to the personal didactic models (MDP) built by novice teachers of Middle Level Biology, through research based on the conceptual generation mode. To do this, we carried out the content analysis of autobiographies, interviews, class observation records, school plans and teaching materials of eight professors graduated from Higher Institutes of Teacher Training (Argentina), with three to five years in the exercise of teaching. Based on this analysis we reconstruct their personal didactic models from their purposes, procedures, strategies, contents, evaluation and considerations on ideas and interests of students, adding the affectivity as an emerging dimension. We carried out the content analysis following chronologically the phases of pre-analysis, use of material, treatment and interpretation of results. We identify regularities and particularities of each case. The regularities emerged as a product of the professional culture; the particularities were associated with the idiosyncrasy and trajectory of each teacher. Given that there is little research on affectivity in its relationship with MDP, we understand that this study constitutes an advance in this line of research.